Hearing from the Forgotten Victims: A Content Analysis of the Consequences of Bernard L. Madoff’s Ponzi Scheme - Homer, Emily M. (Victims & offenders, 2023)
Bernard Madoff’s Ponzi scheme may be one of the most famous in history. The victims included over 15,000 parties. Roughly 130 elected to share their stories in court by filing victim impact statements. In the current study, we performed a content analysis that explored the consequences of victimization as reported in Madoff’s victim impact statements. We found that the consequences of Ponzi scheme victimization included financial, mental or emotional, interpersonal, physical, life trajectory, and a change in trust in the government. The findings indicate that victims would be better served by having quicker responses from the government after victimization. They also benefit from being included in all phases of criminal proceedings.